Effect of pretreatment to the formation of cake layer and membrane structure in the application of ultra filtration cross-flow Membrane for the treatment of oil-water emulsion waste - Suprihanto Notodarmojo; T. Zulkarnain; Dini Mayasanthy; M. Irsyad (Journal of Mathematical and Fundamental Sciences, 2004)
A study on the effect of pretreatment on the use of cellulose acetate (CA) membrane using cross-flow system to treat oil-water emulsion waste came from metal cutting process of an automotive industry has been done. The objectives of this research are to see the impact of pretreatment process to flux and cake forming, indicated by cake forming constant (k'), and to study membrane structure. The ultra filtration process performance was determined by obtaining the values of permeate flux and rejection. The material of membrane used in this process was cellulose acetate membrane with 12 % of cellulose acetate composition for first stage operation and 15 % for second stage operation. The duration of the process was 90 minutes operation time, by applying operation pressure at 3, 5 Bar. There were two types of feeding mode applied, the first was feeding without pretreatment and the second was feeding with pretreatment. After some operation periods, the permeate flux decreases due to fouling. On the first stage of membrane operation, for waste without pretreatment, we obtained the value of k'= 0,0004 m2/L and for waste with pretreatment k'= 0,0001 m2/L. On the second stage membrane operation, for waste without pretreatment the value of k'= 0,0009 m2/L and for waste with pretreatment k'= 0,0002 m2/L. The results mean that pretreatment reduce significantly formation of the cake. It was also obtained that the structure of the membrane is asymmetric. It was shown that deposition of contaminant also occurs within the spinger of the membrane (inner structure of the membrane). Deformation of the membrane spinger was also observed. It is concluded that pretreatment applied to feeding solution increase the running time of the membrane. The benefit of membrane operation used feed with pretreatment, beside increases permeate fluks also decreases the cake forming constant which will longer operation time of membrane.